Review of the genus Cibyra Walker (Lepidoptera: Hepialoidea: Hepialidae) with descriptions of twenty-four new species from Brazil and Argentina - Mielke, Carlos G.c.; Grehan, John R.; Koike, Ricardo M. (Zootaxa, 2025)
The genus Cibyra Walker, 1856 is reviewed. The following species are described as new from Brazil: Cibyra agnes sp. nov., C. alina sp. nov., C. babi sp. nov., C. barbara sp. nov., C. bruna sp. nov., C. clara sp. nov. C. claudia sp. nov., C. denise sp. nov., C. elyana sp. nov., C. hannelore sp. nov., C. jane sp. nov., C. julie sp. nov., C. jurate sp. nov., C. kika sp. nov., C. mariana sp. nov., C. mirna sp. nov., C. monique sp. nov., C. olinda sp. nov., C. parana sp. nov., C. piacaba sp. nov., C. regina sp. nov., C. simone sp. nov., and C. volta sp. nov. Cibyra yumiko sp. nov. is described from Brazil and Argentina. All species are figured along with their genitalia. Dalaca oreas Schaus, 1892, syn. n. is synonymized to Cibyra ferruginosa Walker, 1856. A biogeographic model of ancestral allopatry is proposed for Cibyra species-groups and species through tectonic uplift during the formation of the Atlantic basin. It is suggested that the extensive overlap of species-groups represents taxon crowding resulting from submergence and erosion of coastal landscapes